Campur Kode Dalam Akun Twitter @Saybuddy - Widana Putra, Widana Putra (International Seminar on Austronesian Languages and Literature, 2021)
Twitter as a medium for expressing ideas contains interesting phenomena for linguistic dates, one of which is code mixing. This research was conducted descriptively. The data is taken from the twitter account @saybuddy which was uploaded on 16 and 17 July 2021 as many as nine uploads that damage code mixing. The form of code mixing in the upload is in the form of words, phrases, and clauses. The function of code mixing used is to emphasize, adjust the subject matter, expression, respect and prestige